6(2X+5)-(3-5X)=

Simple and best practice solution for 6(2X+5)-(3-5X)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6(2X+5)-(3-5X)= equation:


Simplifying
6(2X + 5) + -1(3 + -5X) = 0

Reorder the terms:
6(5 + 2X) + -1(3 + -5X) = 0
(5 * 6 + 2X * 6) + -1(3 + -5X) = 0
(30 + 12X) + -1(3 + -5X) = 0
30 + 12X + (3 * -1 + -5X * -1) = 0
30 + 12X + (-3 + 5X) = 0

Reorder the terms:
30 + -3 + 12X + 5X = 0

Combine like terms: 30 + -3 = 27
27 + 12X + 5X = 0

Combine like terms: 12X + 5X = 17X
27 + 17X = 0

Solving
27 + 17X = 0

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '-27' to each side of the equation.
27 + -27 + 17X = 0 + -27

Combine like terms: 27 + -27 = 0
0 + 17X = 0 + -27
17X = 0 + -27

Combine like terms: 0 + -27 = -27
17X = -27

Divide each side by '17'.
X = -1.588235294

Simplifying
X = -1.588235294

See similar equations:

| 20x^3-60x^2+40x=0 | | 5/7=x/200 | | (7x-2)(4x+8)= | | 5/6(-6x-12) | | -100=-2(1+7m) | | 32=2y+8 | | 5+5+6+4+x=23 | | 12-3/5x=-27 | | -9-(8-5d)=18 | | N-(50)=-31 | | 4a-2a=-36 | | 2(-4)+2x=-6x-2 | | 3d+8=-17 | | 120+2y=180 | | 10+7+4=10+7+4 | | P+1-2=7 | | 63=3k | | 6(2X-5)-(3-5X)= | | 4(6x+6)= | | 7a+1-3a-5=3[a+1] | | 9cosx+1=8cosx | | 7n-6n=-6 | | 5/7=x/7000 | | Log(2x+1)=3x-2 | | 1(2+3)=2+3 | | (2t+10)(3s)=180 | | (-5x-1)+2x+3=-4x+5 | | 2(-5x+3)-5x-4=-x+58 | | -8(x+5)=-8x-5(x+5) | | Nz-a=bx+d | | 5x+3x+2=10 | | 5x-17=4z-36 |

Equations solver categories